THE EFFECT OF SIMILARITY IN GENDER ROLE ATTITUDE ON MARITAL SATISFACTION AMONG MIDDLE-AGED COUPLES. (11th November 2018) - Park, H; Jun, H; Joo, S
Abstract: Are similar spouses happier? This study aimed to examine the effect of similarity in gender role attitude on marital satisfaction among middle-aged couples. For the analyses, the Third National Survey of Korean Families was utilized and the sample was 1, 053 couples aged 40 to 60. The dependent variables were husbands' and wives' perceived marital satisfaction and the independent variable was similarity in gender role attitude between husband and wife. Covariates were age, education level, employment status, and number of years since marriage. Latent Profile Analysis was applied to identify the patterns of gender role attitude for each gender with Mplus 7.3. Using the results, similarity in gender role attitude was generated by dummy-coding the coincidence of the pattern between husband and wife. Then, using STATA/SE 13.0, Seemingly Unrelated Regression was applied to analyze the effects of similarity in gender role attitude on husbands' and wives' marital satisfaction. The results indicated that similarity in gender role attitude had a significant effect on wives' marital satisfaction (b=.12, p<.05); wives who had similar gender role attitudes to their husbands were more satisfied with the marital relationship. However, the effect of similarity in gender role attitude on marital satisfaction was not significant for husbands. This study may provide insights to discussions about ways to better promote and understand marital quality in later life. Future studies are needed to explore significant predictors of marital satisfaction for middle-aged husbands and to investigate the effects of similarity in gender role attitude on other couple-related outcomes.